دراسة مسحية - تغذوية لمرض السمنة بين طلاب قسم علوم الحياة – كلية التربية - جامعة ميسان/ العراق - محسن علي وليد (University of Thi-Qar Journal of Science, 2010)
Obesity was studied on a sample of students in Biology Dep. College Of Education Miasn University . Bio mass indicator (BMI) were calculated to 130 students (100 females and 30 males) . Results showed that females suffered from overweight, obesity and over obesity were (25%, 16% and 4% ) respectively . Males suffered from over weight , obesity and over obesity were (20% , 6.66% and 3.33%) respectively . This study showed that (45%) from females were suffered from overweight ,obesity and over obesity while (29.99%) from males were suffered from over weight ,obesity and over obesity .